Complications of diagnostic upper Gastrointestinal endoscopy: common and rare – recognition, assessment and management - Zacharias P Tsiamoulos; Matthew Banks; Bhaskar Kumar; Nigel J Trudgill; Umair Kamran; William Waddingham (BMJ Open Gastroenterology)
A clear understanding of the potential complications or adverse events (AEs) of diagnostic endoscopy is an essential component of being an endoscopist. Creating a culture of safety and prevention of AEs should be part of routine endoscopy practice. Appropriate patient selection for procedures, informed consent, periprocedure risk assessments and a team approach, all contribute to reducing AEs. Early recognition, prompt management and transparent communication with patients are essential for the holistic and optimal management of AEs. In this review, we discuss the complications of diagnostic upper gastrointestinal endoscopy, including their recognition, treatment and prevention.